Deep crustal melt plumbing of Bárðarbunga volcano, Iceland - Hudson, T. S; White, R. S.; Greenfield, T.; Ágústsdóttir, T.; Brisbourne, A.; Green, R. G. (Geophysical Research Letters, 2017)
Understanding magmatic plumbing within the Earth's crust is important for understanding volcanic systems and improving eruption forecasting. We discuss magma plumbing under Bárðarbunga volcano, Iceland, over a 4 year period encompassing the largest Icelandic eruption in 230 years. Microseismicity extends through the usually ductile region of the Earth's crust, from 7 to 22 km depth in a subvertical column. Moment tensor solutions for an example earthquake exhibits opening tensile crack behavior. This is consistent with the deep (>7 km) seismicity being caused by the movement of melt in the normally aseismic crust. The seismically inferred melt path from the mantle source is offset laterally from the center of the Bárðarbunga caldera by ~12 km, rather than lying directly beneath it. It is likely that an aseismic melt feed also exists directly beneath the caldera and is aseismic due to elevated temperatures and pervasive partial melt under the caldera.